DETERMINATION OF THE OPTIMAL CAPITAL INVESTMENTS TO ENSURE THE SUSTAINABLE DEVELOPMENT OF THE RAILWAY - Kharchenko, O. I. (Science and Transport Progress, 2015)
Purpose. Every year more attention is paid for the theoretical and practical issue of sustainable development of railway transport. But today the mechanisms of financial support of this development are poorly understood. Therefore, the aim of this article is to determine the optimal investment allocation to ensure sustainable development of the railway transport on the example of State Enterprise «Prydniprovsk Railway» and the creation of preconditions for the mathematical model development. Methodology. The ensuring task for sustainable development of railway transport is solved on the basis of the integral indicator of sustainable development effectiveness and defined as the maximization of this criterion. The optimization of measures technological and technical characters are proposed to carry out for increasing values of the integral performance measure components. To the optimization activities of technological nature that enhance the performance criteria belongs: optimization of the number of train and shunting locomotives, optimization of power handling mechanisms at the stations, optimization of routes of train flows. The activities related to the technical nature include: modernization of railways in the direction of their electrification and modernization of the running gear and coupler drawbars of rolling stock, as well as means of separators mechanization at stations to reduce noise impacts on the environment. Findings. The work resulted in the optimal allocation of investments to ensure the sustainable development of railway transportation of State Enterprise «Prydniprovsk Railway». This allows providing such kind of railway development when functioning of State Enterprise «Prydniprovsk Railway» is characterized by a maximum value of the integral indicator of efficiency. Originality. The work was reviewed and the new approach was proposed to determine the optimal allocation of capital investments to ensure sustainable development of the State Enterprise «Prydniprovsk Railway». Practical value. Structural reform of Ukrainian railway transport demands to solve problems to improve the efficiency of the industry in the shortest time. The proposed algorithm of investment allocation provides for such a directorate development, the implementation of which will lead to increase of functioning efficiency of the railway transportation directorate, which in turn will positively affect on the industry as a whole.